Days of opportunity : The United States and Afghanistan before the Soviet invasion - Rakove, Robert B., 1977- (New York, USA : Columbia University Press, 2023)
"Long before the calamities of our own age, the United States involved itself deeply in Afghanistan. Harnessing extensive research in U.S. and foreign archives, the historian Rob Rakove traces the remarkable, ultimately tragic story of U.S. engagement in Afghanistan up to the 1979 Soviet invasion. Committed to the preservation of Afghan independence, the United States played an unwitting, destabilizing role in the country, contributing to Afghanistan's emergence as a Cold War battlefield. Most histories of Afghanistan in the Cold War focus on the 1979 Soviet invasion and the country's emergence as a principal battleground in the 1980s. Even as post-Cold War scholarship has substantially corrected prior notions of what motivated Moscow and offered invaluable studies of U.S.-supported development programs in Afghanistan, an overarching treatment of Washington's efforts in Afghanistan remains to be published and the myth of inattention remains intact. The distinction is this: if the United States largely absented itself from pre-cataclysm Afghanistan, it committed at most a sin of omission. If it funded a few token, misconceived aid programs, while Moscow pursued a coherent, aggressive design, that verdict still holds. If, however, the U.S. role has been understated, and Soviet malevolence has been exaggerated, Washington bears considerable responsibility for the disasters that befell Afghanistan at the end of the 1970s. Days of Opportunity chronicles the vibrant years of peaceful Afghan-American relations, beginning in the wake of the Great War, and continuing until the Soviet invasion. It depicts the U.S. relationship with a different Afghanistan: a country largely at peace, which had evaded enlistment in the world wars, and which struck observers as a success story in Cold War nonalignment. It does not treat the collapse of Afghan nonalignment or the failure of the Afghan state as inevitable developments. It is an account of diplomacy and aid across six generally overlooked decades, described by historian Nile Green as the "missing middle" of Afghan history."--
Introduction: A day of opportunity -- A game of hide and seek : the Afghan pursuit of diplomatic relations, 1921-1938 -- We have a rare opportunity : U.S.-Afghan relations amid the world crisis, 1938-1945 -- Preeminence and peril : the American influx and the coming of the Afghan Cold War, 1945-1952 -- "We might be willing to take a chance" : the choice to contest Afghanistan, 1953-1956 -- Anxious coexistence : the aid contest, 1956-1959 -- The crisis era, 1959-1963 -- Reform and retrenchment, 1962-1968 -- The fall of the monarchy, 1968-1973 -- Return to engagement, 1973-1976 -- The end of diplomacy, 1977-1979 -- Conclusion: "Into the jaws of catastrophe".
Includes bibliographical references and index.
Keywords: Afghanistan Foreign Relation; United States Foreign Relation; United States -- Foreign relations -- Afghanistan; Afghanistan -- Foreign relations -- United States; Afghanistan -- Foreign relations -- 20th century; United States -- Foreign relations -- 20th century; Afghanistan -- History -- 20th century